PENCEGAHAN STUNTING MELALUI PEMENUHAN GIZI ANAK DAN PERAN KELUARGA - Iman; Indah; Yulita Rahmawati, Inne; Setianimgsih, Fitri; Nirwana, Rifal; Giopani (Universitas Islam Al-Ihya Kuningan, 2024)
Stunting is short or very short based on length/height for age which is less than -2 standard deviation (SD) on the WHO growth curve which occurs due to an irreversible condition resulting from inadequate nutritional intake and/or recurrent/chronic infections that occur within 1000 HPK . Stunting is a short or very short growth time based on height for ages 0-2 years standard on the WHO growth curve which occurs due to an irreversible condition resulting from inadequate nutritional intake and/or recurrent/chronic infections that occur within 1000 HPK. The prevalence rate of stunting in Indonesia in 2022 according to the Indonesian Nutrition Status Survey (SSGI) is 21.6%, in Majalengka Regency, the results of the Indonesian Nutrition Status Survey (SSGI) are 24.3%. The methods used in this service are observation and interviews. The results of the research showed that there were 10.9% stunting cases in Cicanir Village. Based on the observations, there were indicators of factors causing stunting. The specific intervention indicator is that there is still a lack of targeted toddlers whose growth and development are monitored at the posyandu as seen from the results of the Toddler Weighing Month in August 2022. Of the 99 toddler targets, only 76 toddlers were weighed and 73 toddlers had their height measured. Or if we calculate the prevalence of D/S or toddlers who come, it is compared with the target, which is only 76% and the indicators of environmental sanitation and clean and healthy living behavior are still lacking. The role of the family is very influential in preventing stunting because the family is the child's first role model in everyday life, so it is necessary to provide education to the community through health seminars regarding Stunting Prevention through Fulfilling Child Nutrition and the Role of the Family.